PENGARUH PENYULUHAN KESEHATAN TERHADAP PENGETAHUAN PENCEMARAN SAMPAH MAKROPLASTIK DAN MIKROPLASTIK PADA MAHASISWA PRODI DIII PEREKAM DAN INFORMASI KESEHATAN STIKes IMELDA - Lamtiur Junita Bancin; Johanna Christy (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
Health education is one of the techniques to increase someone’s knowledge level due to the aim of improving knowledge and well understanding regarding microplastic and microplastic pollution. This research aimed to analyze the effect of health education towards the knowledge regarding macroplastic and microplastic pollution among students at the medical record and health major in the college of health sciences Imelda in terms of health education. This research used a quantitative approach with a Quasi-Experimental Study Design of a non-equivalent control group. The population was all the students with the medical record and health information major. The sampling technique used was purposive sampling, all the first-year students. The group of the sample consisted of two groups- the intervention and the control group. The intervention group consisted of 73 people who have given health education. Control group consisted of 73 people who have not given any health education. The statistic test used was the Wilcoxon test. The statistic result on the knowledge variable among the experiment group who had a good knowledge level refer to the pre-test score only 4.1 %. After given health education, the increasing number of people who had a good knowledge level (76.1%). The good knowledge level among the control group only showed 1.4% (pre-test and post-test). The result showed there was a significant increase after given health education among the experiment group (p=0.00). However, another result showed there was no significant difference among the control group (p=1.00). Health education towards macroplastic and microplastic pollution had a significant influence to the knowledge level for students. It is recommended for further research to examine the role of knowledge towards attitudes and behaviors or actions in the management of macro and microplastic waste pollution. Based on the results of the pre-test where respondents still have less and moderate knowledge while the issue of plastic waste in Indonesia requires full attention and more participation from the community from society, it is necessary to get the attention of educational institutions to further elaborate and educate students in pollution macro-plastic and microplastic waste.